KEPUASAN PELANGGAN DAN MINAT WORD OF MOUTH PENGGUNA MICE HOTEL DI SEMARANG - Winda Pinasti, Krisnhoe; Widiyanto, Ibnu (Diponegoro Journal of Management, 2015)
This study is to investigate factors influencing customer satisfaction of Patra Jasa Semarang Convention Hotel MICE’s users. This satisfaction is likely to increase word of mouth intention. Sample size of this study was 150 respondents. By employing purposive sampling method, the questionaires were distributed to Patra Jasa Semarang Convention Hotel MICE’s users from November 2014 until December 2014. The data then were analyzed by using a multiple regression test. The result showed that three of the independent variables directly influencing customer satisfaction, but only one of those which had directly influencing to word of mouth intention, that was quality of food and baverages variable. Consistent with the previous studies, customer satisfaction has positive relation and significantly mediates the effect of independents variables to engage word of mouth intention.